The Effect of Obesity, Oral Contraceptive and Passive Smoking on the Risk of Cervical Cancer - Roiela Arfailasufandi; Ambar Mudigdo; Aris Sudiyanto (Masters Program in Public Health, 2019)
Background: Studies have investigated the effects of obesity on cancer development. However, the relationship between obesity and cervical cancer risk is unclear. This study aimed to determine the effect of obesity, oral contraceptive and passive smoking on the risk of cervical cancer.Subjects and Method: A case-control study was conducted at Dr. Moewardi Hospital, from October to December 2018. A sample of 200 patients was selected by fixed disease sampling, consisting of 100 cervical cancer patients and 100 noncervical cancer patients. The dependent variable was cervical cancer. The independent variables were obesity, oral contraceptive use, smoking exposure, parity, age at first sexual intercourse, and family history. The data were obtained from the medical record. The data were analyzed by multiple logistic regression.Results:The risk of cervical cancer increased with obesity (OR= 6.83; 95%CI= 2.44 to 19.17; p<0.001), cigarette smoke exposure (OR= 12.57; 95% CI= 4.59 to 34.41; p<0.001),oral contra